Malpraktik Kedokteran Gigi dan Pertanggungjawaban Pidana : Tinjauan UU No. 17 Tahun 2023 Tentang Kesehatan: Dental Malpractice and Criminal Liability : A Review Of Law No. 17 Of 2023 On Health - Andriani Fauziah, Yessy; Alhadad, Husin; Agis Susanti, Dany (Jurnal Hukum dan Etika Kesehatan, 2025)
Malpractice cases in dentistry have become an increasingly significant legal issue, particularly regarding the criminal liability of dentists. Law No. 17 of 2023 on Health introduces substantial changes in Indonesia’s health law regulations, including provisions on medical professionals’ legal accountability. This regulation defines the boundaries and sanctions for practices considered negligence or malpractice. This study aims to analyze the criminal liability of dentists in malpractice cases based on the provisions of Law No. 17 of 2023. The research method used is normative legal research based on literature, focusing on relevant regulations and legal concepts. The analysis shows that Law No. 17 of 2023 provides more explicit rules on dentists’ criminal liability. However, ambiguities remain in its implementation, particularly in distinguishing between negligence and malpractice. Additionally, legal protection for dentists facing malpractice allegations needs further clarification when implementing regulations. This study is expected to provide insights for legal practitioners and medical professionals to understand the legal implications of medical actions and offer recommendations for regulatory improvements in the future.